اختبار التكامل المتزامن بين عرض النقود والتضخم في الاقتصاد الجزائري خلال الفترة (1990– 2016) - خنيش, يوسف; لبزة, هشام (جامعة الوادي - University of Eloued, 2022)
The aim of this study is to determine the nature of the causal relationship between money supply and inflation in the Algerian economy during the period 1990-2018, using the Granger methodology to test the causal relationship, and the error correction model to determine the direction of the relationship in the long term. The study found that there is a causal relationship of one direction in the short term, from inflation to M2, The joint cointegration test in the Engel and Granger method between each monetary aggregation and inflation complex in Algeria showed that there was no long-term balance between them
Co- integration test of money supply and inflation in the Algerian economy during the period (1990-2018)
مقال
Keywords: عرض النقود ; التضخم ; سببية جرانجر ; التكامل المتزامن